Targeting Bruton Tyrosine Kinase With Zanubrutinib for Treatment of Vitreoretinal Lymphoma: Report of 3 Cases - Wang, Liang; Guan, Wenxue; Peng, Xiaoyan (Frontiers in Oncology, 2021)
Vitreoretinal lymphoma (VRL) is a rare intraocular malignancy, and standard treatment approaches have not been defined. Bruton tyrosine kinase inhibitors are found to be effective in the treatment of primary central nervous system diffuse large B cell lymphoma. Herein, we retrospectively reported the efficacy and safety of bruton tyrosine kinase inhibitors in three consecutive patients with VRL. All three cases of VRL occurred in patients with pre-treated PCNSL and the central nervous system was not involved at the time of VRL diagnosis. They were treated with zanubrutinib, a bruton tyrosine kinase inhibitor, at 160 mg twice daily orally. Rapid improvement of visual acuity and tumor control was achieved in all involved eyes of these 3 patients. Complete remission was confirmed by fundus photograph and optical coherence tomography, and the level of interleukin-10, a well-recognized biomarker for vitreoretinal lymphoma, decreased to normal in all patients. Zanubrutinib was well tolerated in all three patients, and only one adverse event of grade 3 hypertension occurred, which resolved after adjusting antihypertensive drugs. As of March 2021, these three patients have been treated with zanubrutinib for 9 months, 7 months, and 6 months, respectively, and all remained in complete remission. In conclusion, targeting bruton tyrosine kinase with zanubrutinib in vitreoretinal lymphoma is feasible and our findings can be a foundation for a paradigm shift in treatment options for this rare disease. A prospective phase 2 study evaluating the efficacy and safety of zanubrutinib in patients with vitreoretinal lymphoma is ongoing to validate our findings.